KARAKTER MORFOLOGIS DAN MOLEKULAR Macrobrachium spp. SUNGAI OPAK DI DAERAH ISTIMEWA YOGYAKARTA - , ANITA WIDIANAWATI; , Drs. Trijoko, M.Si ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Daerah Istimewa Yogyakarta (DIY) has several rivers, includes Opak River which its upstream located on Mount Merapi. This river has a lot of biological resources, includes prawns. Freshwater prawns (Macrobrachium spp.) were Crustacean which has important role in maintaining the balance of freshwater ecosystems. In addition, this species also has an economic importance. The purpose of this research was to determine species diversity of Macrobrachium spp. and to understand the morphological and molecular characters of them. Samples were taken from 18 sampling points within 4 station points throughout Opak River. Sampling was carried out in two periods, in the morning and evening for each sampling point. Six species of Genus Macrobrachium were obtained, they are Macrobrachium pilimanus, M. sintangense, M. lanchesteri, M. cowlesi, M. latidactylus, and M. equidens. Phenetic similarity was analyzed using 74 morphological characters and primer ISSR 1 and ISSR 3. The results were then analyzed using a program MVSP 3.1 (Multi- Variate Statistical Package) to obtain a dendogram that showed both intra-and interspesies similarity of Macrobrachium spp. The analysis showed the percentage of phenetic similarity based on morphological characters form two major clusters, consisting of M. equidens and M. lanchesteri as cluster C, and cluster B consisting of M. pilimanus, M. sintangense, M. cowlesi, and M. latidactylus. All branches were combined at 55.6%. The percentage of phenetic similarity based on molecular characters form two major clusters, consisting of M. latidactylus, M. equidens, M. sintangense as cluster C. On the other hand, M. pilimanus, M. cowlesi, and M. lanchesteri considered as cluster D. In which, all branches were combined at 21.52%. From the analysis of phenetic similarity based on morphological and molecular characters, we concluded that phenetic similarity of Macrobrachium spp. in Opak river was affected by the morphological structure of the second pereiopod, habitat type, size and number of eggs, as well as the type of larval development.